In vitro comparison of ICDAS and DIAGNOdent Pen in the diagnosis and treatment decisions of non-cavitated occlusal caries = Comparación In Vitro de ICDAS y DIAGNOdent Pen en el diagnóstico y decisiones de tratamiento de la caries oclusal no cavitada - Akarsu, Serdar; Aktug Karademir, Sultan (2018)
The aim of this study was to compare the efficacy of the ICDAS and the DIAGNOdent Pen in the diagnosis of occlusal caries lesions without cavitation, and for basing treatment decisions on the results obtained. Eighty permanent molar teeth that were healthy and non-cavitated or that had an initial occlusal lesion were evaluated. All teeth were investigated using DIAGNOdent Pen and ICDAS by four examiners. Histological evaluation of teeth was performed using stereomicroscopy by a histologist and different experienced dentist. For evaluation of the data, weighted kappa values (kw), sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratio (LR+) values of the tests were calculated. The diagnostic results obtained using the DIAGNOdent Pen were found to correlate better with the results obtained from histological sections than those obtained using ICDAS. When the treatment decisions of the observers depending on the results of ICDAS, and ICDAS and DIAGNOdent Pen combination were compared with the decisions made based on histological examinations, the decisions based on ICDAS and DIAGNOdent Pen combined (kw: 0.522) were more accurate than the ones based on ICDAS (kw: 0.415) alone. In conclution, professional experience is an effective factor in diagnosing occlusal caries lesions without cavitation with ICDAS and in making treatment decisions for them. DIAGNOdent Pen is sufficient in diagnosing occlusal caries lesions without cavitation.
El objetivo de este estudio fue comparar la eficacia de ICDAS y de DIAGNOdent Pen en el diagnóstico de lesiones de caries oclusales no cavitadas. Ochenta molares permanentes sanos y no cavitados fueron utilizados. Todos los dientes fueron investigados usando DIAGNOdent Pen e ICDAS por cuatro examinadores. La evaluación histológica de los dientes se realizó mediante estereomicroscopía por un histólogo y por un dentista con previa experiencia. Los resultados diagnósticos obtenidos con el DIAGNOdent Pen se correlacionan mejor con los resultados obtenidos a partir de las secciones histológicas cuando comparados a los obtenidos utilizando ICDAS. Las decisiones basadas en el uso combinado de ICDAS y DIAGNOdent Pen (kw: 0.522) fueron más precisas que los basados en ICDAS (kw: 0.415). En conclusión, la experiencia profesional es un factor eficaz en diagnóstico de lesiones de caries oclusal sin cavitación con ICDAS y en la toma de decisiones de tratamiento. DIAGNOdent Pen es una herramienta confiable para diagnosticar lesiones de caries oclusales sin cavitación.
En revista Odóvtos, vol. 20, no. 3 (septiembre-diciembre 2018)
Descripción basada en el contenido visto 01 de agosto, 2024
También disponible en formato HTML
Keywords: CARIES DENTALES -- DIAGNOSTICO; MOLARES